2009
DOI: 10.4174/jkss.2009.77.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of p53, Ki-67 and Galectin-3 Expressions in Papillary Thyroid Carcinoma

Abstract: Purpose: There are few molecular markers useful in practice for predicting prognosis of papillary thyroid carcinoma (PTC) despite numerous basic researches. The objective of this study was to evaluate the prognostic values of several candidate markers of PTC (p53, Ki-67 and galectin-3) using immunohistochemistry (IHC), one of the most practical methods. Methods: IHC for p53, Ki-67 and galectin-3 were performed on formalin-fixed paraffin-embedded tissues of 160 PTC specimens using monoclonal antibodies. The ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the present study, p53 protein overexpression was observed in 47.3% of the PTC. Although several studies have reported finding that detection of p53 protein was a significant and independent prognostic indicator in differentiated thyroid carcinoma (Hosal et al, 1997;Horie et al, 2001;Omar et al, 2004;Morita et al, 2008;Kim et al, 2009;Balta et al, 2012), the association has been a matter of controversy (Park et al, 1998;Kalidag et al, 2007;Jung et al, 2007;Zafon et al, 2007;Cvejic et al, 2008;Hamzany et al, 2012). Hosal et al (1997) reported that p53 protein overexpression was present in cases with extrathyroidal extension and metastases (Hosal et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, p53 protein overexpression was observed in 47.3% of the PTC. Although several studies have reported finding that detection of p53 protein was a significant and independent prognostic indicator in differentiated thyroid carcinoma (Hosal et al, 1997;Horie et al, 2001;Omar et al, 2004;Morita et al, 2008;Kim et al, 2009;Balta et al, 2012), the association has been a matter of controversy (Park et al, 1998;Kalidag et al, 2007;Jung et al, 2007;Zafon et al, 2007;Cvejic et al, 2008;Hamzany et al, 2012). Hosal et al (1997) reported that p53 protein overexpression was present in cases with extrathyroidal extension and metastases (Hosal et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies about immunohistochemical detection of p53 protein showing significant and independent prognostic indicator in differentiated thyroid carcinomas (Hosal et al, 1997;Park et al, 1998;Horie et al, 2001;Omar et al, 2004;Zafon et al, 2007;Morita et al, 2008;Kim et al, 2009;Balta et al, 2012). We investigated the relations between p53 protein expression and the clinicopathologic features and its significance as a diagnostic marker in PTC.…”
Section: Kyung Shin* Jeong Won Kimmentioning
confidence: 99%
See 2 more Smart Citations
“…Gynecomastia can occur due to hypertrophy of the mammary gland (gynecomastia), fat accumulation (false gynecomastia), or complex proliferation. The condition should be treated upon clear understanding of the underlying cause 3 . Subcutaneous mastectomy is the primary method of breast excision.…”
Section: Discussionmentioning
confidence: 99%